Product Leadership - Eriksson, Martin; Walkingshaw, Nate; Banfield, Richard (O'Reilly Media, Incorporated, 2018)
In today's lightning-fast technology world, good product management is critical to maintaining a competitive advantage. Yet, managing human beings and navigating complex product roadmaps is no easy task, and it's rare to find a product leader who can steward a digital product from concept to launch without a couple of major hiccups. Why do some product leaders succeed while others don't?